2018
DOI: 10.1002/cem.3007
|View full text |Cite
|
Sign up to set email alerts
|

Application of SAR methods toward inhibition of bacterial peptidoglycan metabolizing enzymes

Abstract: Structure activity relationship (SAR) methods are applied for a study of inhibition of peptidoglycan metabolizing enzymes, which could represent new antibacterial targets. In this study, we exploit experimental data of inhibition of Mur A and Mur B enzymes for classification of large set of chemicals. Based on inhibitory potency of compounds and their structures from the literature, we developed classification models for new, potential inhibitors of Mur A and Mur B enzymes. The best model for Mur A has the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It is in line with other research that reported a negative correlation between drug-likeness and activity of the compound. There are influencing structural properties contributing to whatever determine active or inactive a compound [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is in line with other research that reported a negative correlation between drug-likeness and activity of the compound. There are influencing structural properties contributing to whatever determine active or inactive a compound [ 44 ].…”
Section: Discussionmentioning
confidence: 99%